ANALISIS BELANJA DAERAH KABUPATEN/KOTA DI BENGKULU - Titik Harliza; Merri Anitasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Titik Harliza, Merri Anitasari:The purpose of this study was to analyze the effect of DAK, DAU and PAD on regional expenditure in Bengkulu. Analysis tools used in this study is Pooled Data Regression with common effect model. The result shows that the variables of Special Allocation Fund (DAK), General Allocation Fund (DAU) and District Original Income (PAD) have significant and positive effect on regional expenditure in Bengkulu.Key Words : Special Allocation Fund (DAK), General Allocation Fund (DAU), District Original Income (PAD), Regional Expenditure, Pooled data regression